2014
DOI: 10.1016/j.neuroimage.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Development of cerebellar connectivity in human fetal brains revealed by high angular resolution diffusion tractography

Abstract: High angular resolution diffusion imaging (HARDI) tractography has provided insight into major white matter pathways and cortical development in the human fetal cerebrum. Our objective in this study was to further apply HARDI tracography to the developing human cerebellum ranging in fetal and adult stages, to outline in broad strokes the 3-dimensional development of white matter and local gray matter organization in the cerebellum. We imaged intact fixed fetal cerebellum specimens at 17 gestational weeks (W), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…This study used HARDI tractography in an attempt to identify degeneration of fiber pathways in the cerebellum. In our previous tractography study on normal human brains, we successfully identified multiple different components of cerebellar fiber pathways at developing ages [14] and in adults [15]. We found that, in the cerebellar cortex, tractography detected tangential coherence superficially in the cerebellar cortex and revealed axonal fibers coursing parallel to the long axis of the folia and thus consistent with the location and orientation of parallel fibers in the molecular layer.…”
Section: Introductionsupporting
confidence: 54%
“…This study used HARDI tractography in an attempt to identify degeneration of fiber pathways in the cerebellum. In our previous tractography study on normal human brains, we successfully identified multiple different components of cerebellar fiber pathways at developing ages [14] and in adults [15]. We found that, in the cerebellar cortex, tractography detected tangential coherence superficially in the cerebellar cortex and revealed axonal fibers coursing parallel to the long axis of the folia and thus consistent with the location and orientation of parallel fibers in the molecular layer.…”
Section: Introductionsupporting
confidence: 54%
“…This in vivo study does not provide the same level of detail of previous ex vivo studies (Takahashi, Hayashi, Schmahmann, & Ellen Grant, 2014; Takahashi et al., 2013) due to the inherit limitations of studying living subjects; however, it may provide a more practical preliminary point of reference for clinical pediatric neuroradiologists. Using the same spatial resolution under the same MR coil across subjects with different ages, smaller brains would likely be more affected by partial volume effects as compared to larger brains.…”
Section: Discussionmentioning
confidence: 94%
“…This explanation of the variations is supported by the observation that MD, RD and AD differentially contributed to changes in FA in the ICP, MCP and SCP. Follow-up studies would be able to explore the contribution of crossing fibers to diffusion properties of cerebellar pathways through the use of complex diffusion models (47, 48). In addition, future studies can correlate FA or other diffusion properties of the peduncles with motor, cognitive or emotional functions in which the cerebellum has been implicated (1, 2, 4, 6, 49).…”
Section: Discussionmentioning
confidence: 99%